ChemInform Abstract: Nickel‐Catalyzed Three‐Component Domino Reactions of Aryl Grignard Reagents, Alkynes, and Aryl Halides Producing Tetrasubstituted Alkenes. Issue 34 (August 2015) - Xue, Fei; Zhao, Jin; Hor, T. S. Andy; Hayashi, Tamio
Abstract A three‐component Ni‐catalyzed coupling reaction of internal alkynes with aryl Grignard reagents and aryl iodides is presented to give fully substituted tetraaryl and triaryl ethenes.